Correlation of expressional pattern of Ubiquitin activating gene with grain Fe content in rice - Bej, Sonali; Neeraja, C N; Krishna Kanth, T; Suman, K; Barbadikar, Kalyani M; Voleti, S R (ORYZA-An International Journal of Rice, 2020)
Ubiquitin, ubiquitin-activating enzyme (E1), ubiquitin-conjugating enzyme (E2), ubiquitin ligases (E3) and 26S proteasome are the significant components of the ubiquitination process. The expression level of ubiquitin activating (UBA) gene was evaluated in 18 genotypes with differential grain iron (Fe) and zinc (Zn) (including landraces, high yielding and released biofortified varieties) at panicle initiation stage. The relative expression of the UBA gene was analysed with three yield checks- BPT 5204, MTU 1010 and Swarna and the highest geneexpression level were found in land race Kalanamak followed by Jalpriya and Taroari Basmati.Significant positive correlation of expression of the UBA gene with grain Fe content suggests the possible role of ubiquitin activating enzymes in addition to the reported ubiquitin-conjugating and ligases in Fe homeostasis. The understanding of ubiquitination regulated nutrient transport mechanism is yet to be explored hence, more indepth studies in future may provide better insight to understand the role of ubiquitination in nutrient homeostasisand develop better strategies for biofortification.